The influence of identity leadership principles on followers' challenge and threat states and motor performance. (May 2021) - Miller, Anthony J.; Slater, Matthew J.; Turner, Martin J.
Abstract: It has been theorized that a follower can draw upon support from individuals they identify with when approaching competitive situations to improve psychophysiological challenge states, and performance potential. As such, we examine how perceptions of identity leadership influence resource appraisals, cardiovascular reactivity, and performance in a pressurised motor task across two laboratory experiments. In Study 1, 80 participants took part in a within-subjects double-blind design with two conditions: identity leadership (IL) vs no identity leadership (no IL). Results indicated that when instructions align with identity leadership principles (vs. not), followers reported greater resource appraisals to, challenge cardiovascular reactivity to, and motor performance within a motivated performance situation. In Study 2, 120 participants completed a 2 (identity leadership: IL vs. no IL) X 2 (appraisal: challenge vs. threat) between-subjects double-blind design. It was found that when instructions aligned to identity leadership (vs. not), followers reported greater resource appraisals and motor performance. When leaders used challenge (vs. threat) instructions this led to challenge cardiovascular reactivity on approach to competition. Advancing leadership and stress theory, we provide evidence that perceived identity leadership is salient for followers' resource appraisals, cardiovascular reactivity, and motor performance. Highlights: Identity leadership promotes positive appraisals of competitive events. Identity leadership promotes physiological challenge states. A lack of Identity leadership did not promote physiological threat states. Identity leadership buffers against the negative effect of ego-threat. Identity leadership promotes effective motor performance.